The Existence of Women in the Batak Angkola Family in North Padang Lawas - Syukur Kholil; Iskandar Zulkarnain; Irma Yusriani Simamora (Budapest International Research and Critics University, 2021)
In fact, women who are born into the world have the same rights as men. However, the reality shows that women who live and settle in North Padang Lawas have different rights and treatment from men. Such unequal treatment is based on existing customs and has been entrenched for a long time in people's daily lives. This paper aims to determine the existence of women in the Batak Angkola family in North Padang Lawas from the perspective of the customs prevailing in North Padang Lawas. The conclusion is that the values, norms and culture that exist in the Batak Angkola community in North Padang Lawas have unconsciously created symbolic violence against women even though they feel that what they experience is not a form of violence. However, it is natural and also a form of devotion and a form of affection for the family. There have been several changes and shifts in the values and cultural norms that exist in the Batak Angkola community of Padang Lawas Utara. The changes and shifts are continuous, some are due to the demands of the times, as well as the higher level of education, experience and acculturation that exist in the Angkola Batak community. Meanwhile, Islam views humans as creatures who have the same basic rights regardless of gender.